Advanced Anti-slug Control for Offshore Production Plants. Issue 6 (2015) - Campos, M.; Takahashi, T.; Ashikawa, F.; Simoes, S.; Stender, A.; Meien, O.
Abstract: The application of advanced control techniques in offshore oil production plants is a challenge. There are many changes in operational points in time, for example, the process is affected by the natural oil well's behavior dynamics. Besides that, limited instrumentation available has to be considered when thinking in oil optimization and control. In order to improve the scenario, taylor-made advanced control modules have been developed for those units. The present article will present development, implementation and results of anti-slug control for three platforms located at Campos and Santos basins. The controllers were designed to achieve improvement in operational stability and safety, decreasing in unscheduled compressor shutdown events, as well as increasing in operational efficiency.